Case Report: Pathologic complete response in a patient with simultaneous diagnoses of resectable NSCLC and myeloid neoplasm with PDGFRA rearrangement treated with concurrent neoadjuvant chemoimmunotherapy and imatinib: translating clinical trial data to real-world practice - Sussman, Chad B.; Shah, Minal; Amin, Kausha; Fanaroff, Rachel; Krause, Eric; Duong, Vu H.; Rosner, Samuel (Frontiers in Oncology, 2025)
Neoadjuvant chemoimmunotherapy has become an established treatment approach in resectable non-small cell lung cancer (NSCLC). The utilization of neoadjuvant immune checkpoint blockade (ICB) and coordination of care in the real-world setting present important challenges, with limited data available for patients with multiple synchronous primary malignancies. This case describes a 57-year-old man with simultaneous diagnoses of resectable stage IIIA NSCLC and PDGFRA-rearranged myeloid neoplasm who received neoadjuvant chemotherapy and nivolumab in combination with imatinib prior to definitive resection. The treatment course was uncomplicated, resulting in a complete pathologic response and resolution of the eosinophilia. Our report highlights the decision-making involved in pursuing combined systemic therapy of the patient’s multiple malignancies and in navigating barriers related to tissue availability for biomarker testing. Approaches to neoadjuvant immunotherapy in early-stage NSCLC can be successful but must remain adaptable to reliably manage complex patient presentations in real-world, non-clinical trial settings.